Colorimetric and Fluorescent Bimodal Ratiometric Probes for pH Sensing of Living Cells. Issue 6 (14th April 2015) - Liu, Yuan‐Yuan; Wu, Ming; Zhu, Li‐Na; Feng, Xi‐Zeng; Kong, De‐Ming
Abstract pH measurement is widely used in many fields. Ratiometric pH sensing is an important way to improve the detection accuracy. Herein, five water‐soluble cationic porphyrin derivatives were synthesized and their optical property changes with pH value were investigated. Their pH‐dependent assembly/disassembly behaviors caused significant changes in both absorption and fluorescence spectra, thus making them promising bimodal ratiometric probes for both colorimetric and fluorescent pH sensing. Different substituent identity and position confer these probes with different sensitive pH‐sensing ranges, and the substituent position gives a larger effect. By selecting different porphyrins, different signal intensity ratios and different fluorescence excitation wavelengths, sensitive pH sensing can be achieved in the range of 2.1–8.0. Having demonstrated the excellent reversibility, good accuracy and low cytotoxicity of the probes, they were successfully applied in pH sensing inside living cells.